The youtubers and the legislation of children's advertising: the scope of the law and the practices observed in channels destined to the children's public - Andrelo, Roseane [UNESP]; Brumatti, Vitor Pachioni (Univ Estadual Paulista Julio Mesquita Filho, Fac Arquitetura Artes & Comun, 2019)
The children's audience is increasingly integrated with the media content present on the Internet and its tools, especially YouTube channels, specifically those that direct their content to children. In this context, this study aims to analyze whether current legislation regarding children's advertising can cover actions and / or advertising insertions on Youtube. The study was carried out through a bibliographical research to construct the theoretical scope and a descriptive research in which three channels of Youtube were selected. Thus, it was possible to compare the practices found in these materials with the legislation regarding children's advertising, especially the verified presence of contents that refer to children's advertising in some formats within the videos analyzed.
Keywords: Children's Advertising; Legislation; YouTube; Youtubers